Pertimbangan Hakim Terkait Perizinan Poligami di Pengadilan Agama Surakarta (Studi Putusan No Perkara 500/Pdt.G/2023/PA.Ska) - Laily Maydiana; Muh. Kurniawan Budi Wibowo; Aditya Fajri Kurnia Pradana (AL HUKMU: Journal of Islamic Law and Economics, 2026)
A polygamous marriage is a marriage of a husband who has more than one wife or a maximum of four wife boundaries which have a legal basis, namely in Al-Qur'an Surah An- Nisa 'verse 4: 3 and also in Law No. 1 of 1974 concerning Marriage in articles 55 to article 59 KHI, polygamy permission must go through the court, this study seeks to explore judges 'considerations in giving decisions regarding polygamy licensing which is the title of the author's thesis is Judges' Considerations Regarding Polygamy Licensing at the Surabaya Religious Court. Number 500/Pdt.G/2023/PA.Ska. As for the formulation of the problem is: What are the main legal considerations that form the basis for a judge to grant permission for polygamy? Second, how does a judge assess compliance with the conditions for polygamy In this study the authors used library research (library research) to examine the judges' considerations contained in the decision Number 500/Pdt.G/2023/PA.Ska. using the KHI perspective and other relevant Reference Analysis. The results of this study show the main legal considerations that form the basis for a judge in granting permission for polygamy, which are the judge's considerations in resolving polygamy cases is Article 4 paragraph 2 letter (a) of the Marriage Law. Article 5 paragraph 1 Marriage Law No. 1 of 1974 and Compilation of Islamic Law Article 58 (paragraph 1 and 2).